Confined Synthesis of Stable and Uniform CsPbBr3 Nanocrystals with High Quantum Yield up to 90% by High Temperature Solid‐State Reaction. Issue 11 (19th March 2021) - Zhang, Qinggang; Zheng, Weilin; Wan, Qun; Liu, Mingming; Feng, Xiuping; Kong, Long; Li, Liang
Abstract: For the display applications of perovskite nanocrystals (NCs), the photoluminescence quantum yield (PLQY), emission linewidth, and operational stability are the main parameters that directly affect the performance of the optoelectronic device. High‐temperature solid‐state synthesis has been regarded as an eco‐friendlier process to prepare perovskite NCs than colloidal synthesis. However, it is relatively difficult to control the sizes and size distribution of NCs at high temperatures, which usually results in a lower PLQY and wider emission. Here, highly stable CsPbBr3 NCs with a high PLQY up to 93% and a narrow emission linewidth of 18 nm are successfully prepared by a hard‐template solid‐state synthesis at high temperature (600 °C). It is found that the precisely confined growth of NCs in the thermally stable and uniform pores of the mesoporous silica (MS) template is the main reason to achieve the high PLQY and narrow emission, and the pre‐hydrolysis sealing strategy contributes to the exceptional stability. More surprisingly, the emission peak intensity of CsPbBr3 /MS@SiO2 is 3.8 times higher than that of the commercialized silicate green phosphor when encapsulated on the blue‐chip with the same absorbance at 450 nm, which makes it an ideal down‐conversion emitter for display applications. Abstract : Highly uniform CsPbBr3 nanocrystals (NCs) with high photoluminescence quantum yield (PLQY) are obtained by a hard‐template confined synthesis at high temperature (600 °C). The CsPbBr3 NCs confined in sealed mesoporous silica (MS) showed high PLQY up to 93%, a narrow emission linewidth of 18 nm and remarkably enhanced stability against water, light, and heat, which make CsPbBr3 /MS@SiO2 a perfect down‐conversion emitter for display applications.